2022
DOI: 10.1002/aesr.202200063
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Polymeric Foams as Flexible Energy Harvesters: A Review

Abstract: Piezoelectric energy harvesters (PEHs) have the potential to power low‐power electronic devices and can advance, self‐powered, autonomous electronics to the next level. Conventional ceramic‐based piezoelectrics have various properties such as fragility, rigidity, toxicity, high density, and lack of design flexibility which limit their use in more flexible environments. A ton of research has been carried out and published on novel piezomaterials, their transduction mechanisms, analytical models, and electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 144 publications
(276 reference statements)
0
7
0
Order By: Relevance
“…[89,144,145] Alternatively, cellular materials can be achieved by sugar-templating strategies and stretching particulate-filled polymers to initiate voids at the filler-polymer interfaces through delamination. [146,147] Piezoelectricity can be induced in such voided materials by ionizing the air pockets by applying a sufficiently high electric field. This can be achieved through direct electrode contact poling, corona discharge poling, or soft X-ray poling.…”
Section: Porous Piezoelectret Elastomer By Foaming Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[89,144,145] Alternatively, cellular materials can be achieved by sugar-templating strategies and stretching particulate-filled polymers to initiate voids at the filler-polymer interfaces through delamination. [146,147] Piezoelectricity can be induced in such voided materials by ionizing the air pockets by applying a sufficiently high electric field. This can be achieved through direct electrode contact poling, corona discharge poling, or soft X-ray poling.…”
Section: Porous Piezoelectret Elastomer By Foaming Techniquesmentioning
confidence: 99%
“…Fang et al reported a cellular PEN piezoelectret fabricated from a commercial PEN polymer film through physical foaming [147] Copyright 2022, Wiley-VCH GmbH. (i) SEM images of the top view, cross-sectional view, and close view of cellular PDMS microstructures.…”
Section: Porous Piezoelectret Elastomer By Foaming Techniquesmentioning
confidence: 99%
“…This result can be explained by the good dispersion of the Cu particles. [46][47][48][49] Furthermore, more enhancement in TC of rigid PU composite may be because of the addition of Cu particles did not create a foam structure inside PU matrix (Table 3). Figure 6 shows DSC thermograms of flexible and rigid PU/Cu composites.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The polymer foam expands its applications in the areas of building insulation, aircraft, automobile, and packaging materials through its light weight, high heat resistance, and noise reduction characteristics. Recently, it enlarged its uses to thermal energy storage, energy harvesting, and bioengineering. …”
Section: Introductionmentioning
confidence: 99%